2019
DOI: 10.2514/1.a34108
|View full text |Cite
|
Sign up to set email alerts
|

Double Asteroid Redirection Test Mission: Heliocentric Phase Trajectory Analysis

Abstract: DART, Double Asteroid Redirection Test, will be the rst mission to demonstrate and characterize the concept of a kinetic impactor for planetary defense, by impacting the smaller member of a binary asteroid system Didymos. Results of this mission will have implications for planetary defense, Near-Earth Object science, and resource utilization. This research focuses on the heliocentric transfer phase of the mission. The heliocentric trajectory is evaluated using various objective functions, including a search fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 8 publications
(5 reference statements)
0
8
0
Order By: Relevance
“…However, Ref. [12] showed that optimizing the kinetic energy at impact (a scalar) was a useful objective that yielded many locally optimal solutions for that mission; therefore, it is reasonable to expect solutions that maximize v imp to also be relevant for maximizing v 2 imp . Second, our calculations examined a range of electrical power levels, including those higher than the capability of the spacecraft.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, Ref. [12] showed that optimizing the kinetic energy at impact (a scalar) was a useful objective that yielded many locally optimal solutions for that mission; therefore, it is reasonable to expect solutions that maximize v imp to also be relevant for maximizing v 2 imp . Second, our calculations examined a range of electrical power levels, including those higher than the capability of the spacecraft.…”
Section: Discussionmentioning
confidence: 99%
“…Asteroid impact missions, such as the Double Asteroid Redirection Test (DART) [8], employ a kinetic impactor to change the orbit of an asteroid. Various publications [9][10][11][12] have evaluated the use of the NASA Evolutionary Xenon Thruster (NEXT) [13] to evaluate design options for the DART mission. The DART mission was launched on 24 November 2021 to impact the Didymos asteroid system 430 days later with an impact speed of 6.58 km/s.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there are several identified strategies with a clear vision for removing a physical body from its original trajectory that have been introduced, such as the kinetic impactor of the Double Asteroid Redirection Test [1], pulverizing hazardous asteroids with a short warning time [2], multifunctional paintball cloud [3], H-reversal trajectory using solar sails [4], and interception missions with a solar sail spacecraft [5], none of the aforementioned strategies can provide accurate solutions from an asteroid mining perspective, although their methods for deflecting PHAs are unique because most of the solutions are from theoretical perspectives and obtaining a whole asteroid from space is impossible. Before it reaches the atmosphere of Earth, it has already disintegrated.…”
mentioning
confidence: 99%